Two women living together - Kim, Hana, 1976-; Hwang, Sunwoo (Ecco, an imprint of HarperCollinsPublishers, 2026)
"When most of their peers were moving in with romantic partners and having children, Kim Hana and Hwang Sunwoo chose independence--savoring solitude, quiet mornings, and the unmitigated freedom of living alone. But in their forties, something shifted, and they were met with a new, unexpected loneliness. Refusing to settle for the outdated choice between marriage or isolation, Hana and Sunwoo made a radical decision: to buy a home and live together--not as lovers, not as roommates, but as chosen family. Now a bustling household of two women and four cats, Hana and Sunwoo still value solitude, but can do so while sharing a life and its meaning with someone else. Together they navigate the challenges and comforts of cohabiting in midlife, the growing pains of interdependence and the unexpected rewards of compromise when you've grown set in your ways. From sick days to career wins to aging parents and beach-side retirement plans, they are redefining domestic bliss on their own terms, where love, partnership, and home are defined not by tradition, but by choice"--